(untitled) - Dumbrell, William J.; (1926-2016) (U.S.A, 2002)
Dumbrell traces the theological movement of each Old Testament book through the Hebrew canonical sequence of Law, Prophets, and Writings, `the manner in which Israel presented her faith.` He not only brings forth insightful points and themes within each book, but he also makes original and refreshing connections to themes in other Old Testament books. This in turn leads to a discussion of the theology of the entire Old Testament canon.
Keywords: Bible -- Old Testament -- Theology